Hubungan Efikasi Diri dengan Psychological Preparedness pada Calon Lulusan Rumpun Ilmu Kesehatan - M. Syahbian Anugrah; Rani Armalita; Septi Mayang Sarry (UNS Press, 2025)
This study aims to examine the relationship between self-efficacy and psychological preparedness for disasters among prospective graduates in health-related fields. The method employed was a quantitative approach with a correlational design. The study sample consisted of 322 prospective graduates, obtained using disproportionate stratified sampling from seven health-related study programs, namely Nutrition, Nursing, Midwifery, Dentistry, Public Health, Medical Education, and Psychology. Data were collected using the General Self-Efficacy Scale (GSES) to measure self-efficacy and the Psychological Preparedness for Disaster Threat Scale (PPDTS) to measure psychological preparedness. The reliability coefficients were .889 for the GSES and .909 for the PPDTS. Data analysis using the Pearson Product-Moment correlation test yielded a significance value of p < .001 with a correlation coefficient of r = .434. These findings indicate a significant positive moderate correlation between self-efficacy and psychological preparedness among prospective graduates in health-related fields. In other words, the higher the prospective graduates' self-efficacy, the higher their psychological preparedness for disasters.